Analisis risiko reputasi terhadap kepercayaan nasabah pada perbankan syari’ah di indonesia - Hardanti, Kandita Deswira (Maliki Interdisciplinary Journal, 2026)
In banking operations, particularly in Islamic banking, risk is inevitable because it is inherent in every operational activity, from fund mobilization to fund disbursement. One of the risks identified in POJK No. 65 is reputational risk. Reputational risk arises due to negative public sentiment and ineffective bank communication strategies, which are often covered by the media and thus become known to the general public (Nugraha, 2019). Negative publicity regarding a bank will inevitably tarnish the bank’s reputation and erode the trust of Islamic banking customers. The purpose of this study is to serve as a learning tool for staff and to raise awareness among customers. This article employs a descriptive qualitative method focused on the implementation of reputation-based risk management. The research findings indicate that the effective implementation of reputation risk management is capable of maintaining the stability of Islamic banking.